The Sacred and the Sensual - Swetha Vijayakumar (Via@)
While most temples in India are considered to be sacred sites for pilgrimage and worship, a group of twenty-two temples at Khajuraho, a small town in central India, have gained much international prominence for the thousands of erotic carvings that saturate its exterior walls. Khajuraho thrives on the dichotomy of being damned as pornography and the transgression of Indian culture on one hand, and on the other being endorsed to international tourists and Indian urban elites as an epitome of Indian liberalness – as the quintessential Kamasutra Temple. Deifying eroticism and promoting tourism using sensual imagery by an otherwise puritanical government in a fairly conservative Indian society is complex, paradoxical, and riddled with contradictions. This paper discusses the process of eroticization occurring at Khajuraho – a process that is a unique amalgamation of religion, culture, and tourism. Drawing from Indian government’s advertisement strategies, marketing of erotic souvenirs, tourist surveys, and statistical data obtained from the ministry of Indian tourism, I identify three distinct ways in which eroticization occurs at Khajuraho: first, through a uniquely romanticized marketing by Indian tour operators who offer enticing honeymoon and holiday packages; second, through the abundance of erotic souvenirs sold on the streets as a symbol of Khajuraho; and third, through the creation of an “experience economy” supported by local prostitution. Visiting a remote and highly eroticized site like Khajuraho, despite it being a Hindu temple, results in a distinctive touristic behavior that is uncharacteristic for any Indian tourism site. At Khajuraho, I contend that all tourists irrespective of their nationalities are foreign.